The Influence of the Covid-19 Outbreak on the Open Unemployment Rate and Economic Growth in the Affected Sectors in Indonesia - Ariodillah Hidayat; Dirta Pratama Atiyatna; Dwi Darma Puspita Sari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Covid-19 outbreak that spreads to almost all countries in the world is predicted to have a huge impact on world economic growth. In early 2020, there were many disasters ranging from floods, natural disasters such as tornadoes, landslides, mountain eruptions, tidal waves or abrasion, forest and land fires and also earthquakes. This study used a simple linear regression analysis method. Simple regression analysis is used to find out the relationships and influences that exist on variables bound to free variables carried out with time series data. The results of the study that the Open Unemployment Rate (TPT) and Economic Growth. dependent var 2.394632. If the economic growth variable is fixed or 0 then the open displacement rate variable is 7.50 percent. The remainder (91.52 percent) is explained by other variables that do not participate in the regression model. The impact of the Covid-19 pandemic or coronavirus is felt by all sectors including the economic sector which results in workers and business people losing income. The weakening economy has an impact on the employment situation in Indonesia. The decline in the rate of economic growth affects the economic performance of all provinces, regencies/cities.